Production process of hard alloy micropore wire drawing die

By adopting high-quality materials and advanced processes, the cemented carbide microporous wire drawing die core has been successfully developed, which has solved the problems of research and development and production of cemented carbide microporous wire drawing die core products in the existing technology, and achieved high-precision drawing and Performance improvement.

CN119500800APending Publication Date: 2025-02-25ANDISON (SUZHOU) CEMENTED CARBIDE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411505023.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-25

Smart Images

  • Figure BDA0005103700220000071
    Figure BDA0005103700220000071
  • Figure BDA0005103700220000081
    Figure BDA0005103700220000081
Patent Text Reader

Abstract

The invention discloses a production process of a hard alloy micropore wire-drawing die, and relates to the technical field of hard alloy micropore wire-drawing dies. According to the technical scheme, the inhibitor is fused in the manufacturing process of the wire-drawing die to refine WC grains and further improve the overall performance of the wire-drawing die, the nickel-chromium-chromium carbide composite powder is introduced, the eutectic temperature of a system can be effectively reduced through the powder, and the densification process of the alloy can be completed under the relatively low temperature condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hard alloy micro-hole wire drawing dies, in particular to a production process of a hard alloy micro-hole wire drawing die. Background Art

[0002] The metal drawing process, as a key technology in the field of metal processing, is centered on drawing metal blanks into filaments or wires through wire drawing dies. In this process, the material and performance of the wire drawing die have a crucial impact on the drawing efficiency, product quality and production cost. At present, the mainstream wire drawing die materials on the market mainly include diamond core, polycrystalline wire drawing die and cemented carbide wire drawing die, each of which has its own advantages, but also has certain limitations.

[0003] Diamond cores, with their excellent wear resistance and hardness, have become the best materials for wire drawing dies. During the metal drawing process, diamond cores can maintain high precision and finish for a long time, ensuring that the drawn wire has stable dimensions and smooth surface. However, the high cost of diamond cores is a major obstacle to their widespread application. In addition, diamonds may degrade in performance under high temperatures or highly corrosive environments, which also limits their use in certain specific scenarios.

[0004] Polycrystalline wire drawing dies have occupied a place in the field of metal drawing with their high hardness and wear resistance. Especially in high temperature environments, polycrystalline wire drawing dies can maintain stable performance and are suitable for drawing difficult-to-process metal wires such as tungsten and molybdenum. However, when used to draw steel-like metal wires, polycrystalline wire drawing dies may cause embrittlement, necking, and wire breakage of the steel wire. These problems not only reduce the quality of the steel wire, but also increase production costs and scrap rates, which limits the use of polycrystalline wire drawing dies in the drawing of steel-like metal wires.

[0005] In contrast, carbide wire drawing dies have been widely used in the field of metal drawing due to their excellent comprehensive performance. Carbide wire drawing dies have high hardness and toughness, and can withstand large drawing forces and friction while maintaining good dimensional accuracy and surface finish. This makes carbide wire drawing dies particularly suitable for drawing high-strength prestressed steel wires and other high-quality metal wires. However, in the research and development and production of microporous wire drawing dies, carbide wire drawing dies face huge challenges. Due to the extremely high material requirements and the difficulty of forming, the research and development and production of carbide microporous wire drawing die core products have been blank in China.

[0006] Aiming at this technical bottleneck, after long-term technical accumulation and R&D innovation, we have successfully broken through the manufacturing technology of cemented carbide micro-hole wire drawing dies. This application adopts advanced production technology and high-quality materials to successfully develop cemented carbide wire drawing die core products with a hole diameter of less than 0.20mm. These products not only have excellent hardness and toughness, but also can meet the high-precision drawing requirements of fine metal wires. Their successful launch not only fills the technical gap of domestic cemented carbide micro-hole wire drawing die core products, but also injects new vitality into the development of the metal processing industry. Summary of the invention

[0007] The purpose of the present invention is to provide a production process of a cemented carbide microporous wire drawing die to solve the problems existing in the prior art.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0009] A hard alloy microporous wire drawing die comprises, by weight percentage, 88-89% of ultrafine WC powder, 9-10% of Co powder, 0.75-1% of nickel-chromium-chromium carbide composite powder and 0.5-1% of chromium oxide powder.

[0010] As an optimization, the particle size of the nickel-chromium-chromium carbide composite powder is 20-50 nm, and the particle size of the chromium oxide powder is 20-30 nm.

[0011] As an optimization, the ultrafine WC powder has a particle size of 2-5 μm and a C content of 5.9-6.0%.

[0012] As an optimization, the particle size of the Co powder is 2-3 μm, and the purity is greater than 99%.

[0013] A production process of a cemented carbide microporous wire drawing die comprises the following steps:

[0014] S1. Weigh the materials according to the above weight percentages, add one-third of WC powder, nickel-chromium-chromium carbide composite powder and chromium oxide powder into a ball mill for pre-grinding for 4 to 6 hours, add Co powder and the remaining two-thirds of WC powder after pre-grinding for 28 to 30 hours, and take out the liquid slurry for standby use after ball milling;

[0015] S2, drying the liquid slurry prepared in S1 at a temperature of 60 to 80° C. for 45 to 55 minutes, sieving after drying, and adding paraffin wax 0.03 to 0.04 times the mass of the sieved powder to the sieved powder, mixing evenly, drying at a temperature of 60 to 70° C. for 1 to 1.5 hours after mixing evenly, and performing compression molding at a pressure of 6 to 8 MPa after drying, leaving a central hole during the compression molding process, and drying for 10 to 16 hours after compression molding;

[0016] S3. The material after drying in S2 is punched through the center hole by a semi-processing tool to obtain a mold core blank; the mold core blank is placed in a vacuum degreasing sintering furnace, vacuum heated, and debinded for 1 to 1.5 hours at a pressure of 40 to 60 Pa and a temperature of 400 to 600°C. After debinding, it is sintered at a temperature of 1400 to 1450°C. After sintering, it is cooled to room temperature and then carburized to obtain a microporous wire drawing die carbide mold core.

[0017] As an optimization, the ball-to-material ratio in the ball milling process is 3-3.25:1, the rotation speed is 60-70 r / min, the liquid-to-solid ratio is 280-300 mL / kg, the liquid medium is anhydrous ethanol, and the solid medium is a cemented carbide ball with a diameter of

[0018] As an optimization, the sieve aperture during the screening process in S2 is 30 to 100 meshes.

[0019] As an optimization, the semi-processing tool material is polycrystalline diamond with a chamfer of 80 to 100°.

[0020] As an optimization, the carburizing treatment in S3 includes the following steps: placing the mold core blank and the carburizing agent that have been sintered and cooled to room temperature in a graphite boat, and performing carburizing treatment at a temperature of 1400 to 1450° C. for 1 to 1.2 hours.

[0021] As an optimization, the carburizing agent includes 30-50% aluminum oxide, 10-30% charcoal, and 30-50% barium carbonate by mass percentage.

[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0023] This technical solution incorporates inhibitors into the manufacturing process of the wire drawing die, aiming to refine the WC grains and thus improve the overall performance of the wire drawing die. In particular, a nickel-chromium-chromium carbide composite powder is introduced, which can effectively reduce the eutectic temperature of the system, so that the densification process of the alloy can be completed under relatively low temperature conditions. In the liquid phase sintering stage, the nickel-chromium-chromium carbide composite powder will be completely dissolved in the bonding phase, and then the high melting point W and other elements will be tightly combined with the non-metallic atoms to form a stable atomic group structure, in which carbon atoms occupy the core position, and the high melting point elements constitute the outer protective layer of the atomic group. This structure greatly limits the process of WC grains migrating and growing through the liquid phase to adjacent grains. In the cooling stage, the nickel-chromium-chromium carbide composite powder will also gather at the WC-Co interface, preventing the precipitated W and C atoms from being re-adsorbed onto the original WC particles, thereby forming a tiny step-like structure at the interface. In addition, the composite powder can also effectively inhibit the dissolution of WC in Co. In summary, the nickel-chromium-chromium carbide composite powder exhibits an inhibitory effect on WC grain growth at multiple levels, and its grain refinement effect is more significant than that of simple chromium carbide.

[0024] However, experimental data also reveal its potential negative impact. In the cemented carbide to which nickel-chromium-chromium carbide composite powder is added, the porosity increases, and the bending strength of the alloy declines. This is mainly because the nickel-chromium-chromium carbide composite powder is easily oxidized, and the generated oxide lumps are not easily infiltrated by the liquid bonding phase, which in turn affects the full flow of the bonding phase, resulting in an increase in the internal porosity of the alloy, and may even form a loose organizational structure, which has an adverse effect on the bending strength of the cemented carbide. At the same time, the directional precipitation of nickel-chromium-chromium carbide at the WC-Co interface is also not conducive to the close combination of WC and Co and the uniform distribution of the bonding phase, which further has a negative impact on the performance of the alloy. In order to alleviate these problems, the present application attempts to add an appropriate amount of chromium oxide powder, in order to effectively control the content of harmful substances introduced during the addition process, and to avoid increasing the porosity due to the introduction of oxygen impurities. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] S1. Weigh the materials according to the above weight percentage, add one-third of WC powder, nickel-chromium-chromium carbide composite powder and chromium oxide powder into a ball mill for pre-grinding for 4 hours, add Co powder and the remaining two-thirds of WC powder after pre-grinding for 28 hours, and take out the liquid slurry for standby use after ball milling; during the ball milling process, the ball-to-material ratio is 3:1, the rotation speed is 60r / min, the liquid-to-solid ratio is 280mL / kg, the liquid medium is anhydrous ethanol, and the solid medium is a cemented carbide ball with a diameter of ;

[0028] S2, the liquid slurry prepared in S1 is dried at a temperature of 60°C for 45 minutes, sieved after drying, and paraffin wax 0.03 times the mass of the sieved powder is added to the sieved powder, mixed evenly, dried at a temperature of 60°C for 1 hour after mixing evenly, and molded at a pressure of 6MPa after drying, leaving a center hole during the molding process, and dried for 10 hours after molding; the sieve aperture during the sieving process is 30 mesh; the semi-processed tool material is polycrystalline diamond, with an 80° chamfer;

[0029] S3, the material after drying in S2 is drilled through the center hole by a semi-processing tool to obtain a mold core blank; the mold core blank is placed in a vacuum degreasing sintering furnace, vacuum heated, and debinded for 1 hour at a pressure of 40Pa and a temperature of 400°C. After debinding, it is sintered at a temperature of 1400°C, and after sintering, it is cooled to room temperature and then carburized to obtain a microporous wire drawing die carbide mold core. The carburizing treatment includes the following steps: the mold core blank and the carburizing agent that have been sintered and cooled to room temperature are placed in a graphite boat, and carburized for 1 hour at a temperature of 1400°C; the carburizing agent includes 40% alumina, 30% charcoal, and 30% barium carbonate by mass percentage.

[0030] Example 2

[0031] S1. Weigh the materials according to the above weight percentage, add one-third of WC powder, nickel-chromium-chromium carbide composite powder and chromium oxide powder into a ball mill for pre-grinding for 5 hours, add Co powder and the remaining two-thirds of WC powder after pre-grinding for 30 hours, and take out the liquid slurry for standby use after ball milling; during the ball milling process, the ball-to-material ratio is 3.25:1, the rotation speed is 65r / min, the liquid-to-solid ratio is 290mL / kg, the liquid medium is anhydrous ethanol, and the solid medium is a cemented carbide ball with a diameter of ;

[0032] S2, the liquid slurry prepared in S1 is dried at a temperature of 70°C for 50 minutes, sieved after drying, and paraffin wax 0.035 times the mass of the sieved powder is added to the sieved powder, mixed evenly, dried at a temperature of 65°C for 1.2 hours after mixing evenly, and molded at a pressure of 7MPa after drying, leaving a central hole during the molding process, and dried for 13 hours after molding; the sieve aperture during the sieving process is 80 mesh; the semi-processed tool material is polycrystalline diamond, with a 90° chamfer;

[0033] S3, the material after drying in S2 is drilled through the center hole by a semi-processing tool to obtain a mold core blank; the mold core blank is placed in a vacuum degreasing sintering furnace, vacuum heated, and debinded for 1.2 hours at a pressure of 50Pa and a temperature of 500°C. After debinding, it is sintered at a temperature of 1425°C, cooled to room temperature after sintering, and then carburized to obtain a microporous wire drawing die carbide mold core. The carburizing treatment includes the following steps: the mold core blank and the carburizing agent that have been sintered and cooled to room temperature are placed in a graphite boat, and carburized for 1.1 hours at a temperature of 1425°C; the carburizing agent includes 40% alumina, 20% charcoal, and 40% barium carbonate by mass percentage.

[0034] Example 3

[0035] S1. Weigh the materials according to the above weight percentage, add one-third of WC powder, nickel-chromium-chromium carbide composite powder and chromium oxide powder into a ball mill for pre-grinding for 6 hours, add Co powder and the remaining two-thirds of WC powder after pre-grinding for 30 hours, and take out the liquid slurry for standby use after ball milling; during the ball milling process, the ball-to-material ratio is 3.25:1, the rotation speed is 70r / min, the liquid-to-solid ratio is 300mL / kg, the liquid medium is anhydrous ethanol, and the solid medium is a cemented carbide ball with a diameter of ;

[0036] S2, the liquid slurry prepared in S1 is dried at a temperature of 80°C for 55 minutes, sieved after drying, and paraffin wax 0.04 times the mass of the sieved powder is added to the sieved powder, mixed evenly, dried at a temperature of 70°C for 1.5 hours after mixing evenly, and molded at a pressure of 8MPa after drying, leaving a center hole during the molding process, and dried for 16 hours after molding; the sieve aperture during the sieving process is 100 mesh; the semi-processed tool material is polycrystalline diamond, 100° chamfer;

[0037] S3, the material after drying in S2 is drilled through the center hole by a semi-processing tool to obtain a mold core blank; the mold core blank is placed in a vacuum degreasing sintering furnace, vacuum heated, and debinded for 1.5 hours at a pressure of 60Pa and a temperature of 600°C. After debinding, it is sintered at a temperature of 1450°C, cooled to room temperature after sintering, and then carburized to obtain a microporous wire drawing die carbide mold core. The carburizing treatment includes the following steps: the mold core blank and the carburizing agent that have been sintered and cooled to room temperature are placed in a graphite boat, and carburized for 1.2 hours at a temperature of 1450°C; the carburizing agent includes 50% alumina, 30% charcoal, and 50% barium carbonate by mass percentage.

[0038] Test Example 1

[0039] Cemented carbide was prepared according to the steps in Example 2. The relevant ingredients are shown in Table 1 below. In terms of weight percentage, 10% of Co powder is fixed and remains unchanged. Except for the following inhibitors, the remaining materials are WC powder.

[0040] Table 1 Powder ingredients

[0041]

[0042] The materials were weighed according to the weight percentage in Table 1 above, and after preparing the cemented carbide according to the steps in Example 2, the hardness and bending strength of the cemented carbide were measured;

[0043] After rough grinding, fine grinding and polishing, the sample is tested according to GB / T 7997-2014 hard alloy Vickers hardness test method, with a test force of 30Kgf, a test force application time of 2 to 8 seconds, and a holding time of 10 to 15 seconds. Test six times on each sample. The center distance between two adjacent indentations is not less than 2.5 times the average value of the indentation diagonal, and the Vickers hardness value is found in the appendix;

[0044] According to GB / T 3851-2015, the bending strength of the alloy was measured by the three-point bending method; the measurement results are shown in Table 2 below;

[0045] Table 2 Measurement results

[0046]

[0047] From the above data, it can be seen that the hardness of cemented carbide increases with the increase of the amount of nickel-chromium-chromium carbide composite powder and chromium oxide powder added, but after increasing to a certain extent, it shows a downward trend. In addition, excessive addition of nickel-chromium-chromium carbide composite powder and chromium oxide powder will also affect other mechanical properties. Therefore, it is not possible to improve the alloy performance by simply increasing the content of nickel-chromium-chromium carbide composite powder and chromium oxide powder, and the performance effect is not good during the single addition process. Therefore, the two are finally selected to be used in combination to produce a synergistic effect.

[0048] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A cemented carbide microporous wire drawing die, characterized in that: Calculated by weight percentage, the invention comprises 88-89% of superfine WC powder, 9-10% of Co powder, 0.75-1% of nickel-chromium-chromium carbide composite powder and 0.5-1% of chromium oxide powder.

2. The cemented carbide microporous wire drawing die according to claim 1, characterized in that: The particle size of the nickel-chromium-chromium carbide composite powder is 20-50 nm, and the particle size of the chromium oxide powder is 20-30 nm.

3. The cemented carbide microporous wire drawing die according to claim 1, characterized in that: The ultrafine WC powder has a particle size of 2-5 μm and a C content of 5.9-6.0%.

4. The cemented carbide microporous wire drawing die according to claim 1, characterized in that: The Co powder has a particle size of 2-3 μm and a purity of more than 99%.

5. A production process of a cemented carbide microporous wire drawing die, characterized in that: The following steps are involved: S1. Weigh the materials according to the above weight percentages, add one-third of WC powder, nickel-chromium-chromium carbide composite powder and chromium oxide powder into a ball mill for pre-grinding for 4 to 6 hours, add Co powder and the remaining two-thirds of WC powder after pre-grinding for 28 to 30 hours, and take out the liquid slurry for standby use after ball milling; S2, drying the liquid slurry prepared in S1 at a temperature of 60 to 80° C. for 45 to 55 minutes, sieving after drying, and adding paraffin wax 0.03 to 0.04 times the mass of the sieved powder to the sieved powder, mixing evenly, drying at a temperature of 60 to 70° C. for 1 to 1.5 hours after mixing evenly, and performing compression molding at a pressure of 6 to 8 MPa after drying, leaving a central hole during the compression molding process, and drying for 10 to 16 hours after compression molding; S3. After the material is dried in S2, the center hole is drilled through by a semi-processing tool to obtain a mold core blank; the mold core blank is placed in a vacuum degreasing sintering furnace, vacuum heated, and debinded for 1 to 1.5 hours at a pressure of 40 to 60 Pa and a temperature of 400 to 600°C. After debinding, it is sintered at a temperature of 1400 to 1450°C. After sintering, it is cooled to room temperature and then carburized to obtain a microporous wire drawing die carbide mold core.

6. The production process of cemented carbide microporous wire drawing die according to claim 5, characterized in that: In the ball milling process, the ball-to-material ratio is 3-3.25:1, the rotation speed is 60-70 r / min, the liquid-to-solid ratio is 280-300 mL / kg, the liquid medium is anhydrous ethanol, and the solid medium is a hard alloy ball with a diameter of 7. The production process of cemented carbide microporous wire drawing die according to claim 5, characterized in that: During the screening process in S2, the sieve mesh has a pore size of 30 to 100 meshes.

8. The production process of cemented carbide microporous wire drawing die according to claim 5, characterized in that: The semi-processed tool material is polycrystalline diamond, with a chamfer of 80 to 100 degrees.

9. The production process of cemented carbide microporous wire drawing die according to claim 5, characterized in that: The carburizing treatment in S3 comprises the following steps: placing the mold core blank and the carburizing agent that have been sintered and cooled to room temperature in a graphite boat, and performing carburizing treatment at a temperature of 1400 to 1450° C. for 1 to 1.2 hours.

10. The production process of cemented carbide microporous wire drawing die according to claim 9, characterized in that: The carburizing agent comprises 30-50% of aluminum oxide, 10-30% of charcoal and 30-50% of barium carbonate in terms of mass percentage.